Neuroprotective effects of creatine supplementation in mild TBI management among contact sport athletes: A scoping review - John E. Giraldo; Diego A. Bonilla; Luis F. Bedoya; Katherine F. Hoyos; Santiago G. Velasquéz; Mayra M. Márquez; Jorge L. Petro (Journal of the International Society of Sports Nutrition)
Background Mild traumatic brain injuries (TBI), commonly known as concussions, pose a global public health concern, especially among athletes in contact or collision sports. These injuries not only impact neurocognitive function but also lead to metabolic disruptions, including decreased cerebral creatine concentrations. Given creatine’s critical role in energy metabolism within neural tissue, its supplementation may support recovery by stabilizing these metabolic alterations. This scoping review aims to explore the available evidence on the potential neuroprotective effects of creatine supplementation in the management of TBI in athletes participating in contact sports.Methods A search was conducted in PubMed/MEDLINE and Scopus following the PRISMA for Scoping Reviews (PRISMA-ScR) methodology; key descriptors were combined with Boolean operators, for example: (“creatine” OR “creatine monohydrate”) AND (“contact athlete” OR “contact sport”) AND (“brain concussion” OR “head injury” OR “traumatic brain injury” OR “repetitive head impact”). Quantitative and qualitative studies using animal or human models published in English or Spanish since 2000 were included, provided they reported potential therapeutic effects of creatine supplementation in managing TBI. Studies that did not report metabolic or neurocognitive outcomes were excluded.Results A total of 52 studies were found, four studies met all the inclusion criteria two of the four studies focused on animal models, and two on contact sport athletes; in animal models (rats and mice), creatine supplementation significantly reduced lactate accumulation and post-injury tissue damage, indicating a potential neuroprotective effect. In studies involving contact sport athletes, creatine was integrated into nutritional protocols to aid concussion recovery, with observed variations in the N-acetylaspartate/creatine ratio highlighting a potential role in restoring cerebral metabolism.Conclusion Although the evidence is limited, findings from animal models and contact sports athletes suggest that creatine supplementation may help mitigate the metabolic disturbances associated with concussions. Further human studies are needed to establish optimal supplementation protocol (e.g., dosage, timing, co-supplementation) and to evaluate long-term neurocognitive and metabolic recovery outcomes, thereby confirming its efficacy as a complementary intervention in concussion management.Disclosures DAB serves as member of the “Creatine for Health” scientific advisory board.